2014
DOI: 10.1007/s10815-014-0297-x
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of infertility treatment in patients undergoing assisted reproductive technology after conservative therapy for endometrial cancer

Abstract: Purpose To elucidate the problems in infertility treatment for women after conservative therapy for endometrial cancer (EC) or atypical complex endometrial hyperplasia (ACEH). Methods The clinical outcomes of 21 patients who underwent assisted reproductive technology after conservative therapy (group A) and 42 control women (group B) were retrospectively analyzed. Results There was no significant difference in the number of retrieved oocytes, fertilization rate or the number of transferred embryos between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 18 publications
(18 reference statements)
2
27
0
Order By: Relevance
“…Therefore, it is necessary to minimize damage to normal endometrium. To this end, Fujimoto et al [ 27 , 28 ] suggested that hysteroscopic resection of early stage EC combined with hormonal therapy might be more effective than endometrial curettage for eliminating lesions in such patients hoping to preserve their fertility. Such an approach would minimize a specimen, but does not increase the risk of peritoneal dissemination [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to minimize damage to normal endometrium. To this end, Fujimoto et al [ 27 , 28 ] suggested that hysteroscopic resection of early stage EC combined with hormonal therapy might be more effective than endometrial curettage for eliminating lesions in such patients hoping to preserve their fertility. Such an approach would minimize a specimen, but does not increase the risk of peritoneal dissemination [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors recommend that such patients should undergo fertility examinations and treatment as soon as possible after MPA therapy. Various studies have reported successful deliveries after conservative treatment . In addition, some studies have indicated that fertility treatment after conservative treatment for EC or AH results in better pregnancy outcomes, compared with expectant management; however, the sample sizes of these studies were small and the accumulation of further studies is needed in order to allow firm conclusions to be drawn.…”
Section: Introductionmentioning
confidence: 99%
“…There are reports of many pregnancies after conservative management of endometrial carcinoma, some after ART (Fujimoto et al ., 2014; Koskas et al ., 2014) Combining conservative treatment with ART may result in healthy infants without an adverse effect on oncologic prognosis (Elizur et al. , 2007; Bozdag et al, 2009; Mao et al .,2010).…”
Section: Introductionmentioning
confidence: 99%
“…Ovulation induction does not appear to be associated with increased risk of relapse, and subsequent pregnancies do not worsen oncological outcomes (Matthews et al ., 2012; Fujimoto et al ., 2014; Zapardiel et al ., 2016). The impact of high serum estradiol levels on endometrial carcinoma is uncertain, although some data suggest an adverse effect of ovarian stimulation.…”
Section: Introductionmentioning
confidence: 99%